2009
DOI: 10.1073/pnas.0808347106
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of gene regulation by a cell-specific transcriptional activator

Abstract: The architectural layout of a eukaryotic RNA polymerase II core promoter plays a role in general transcriptional activation. However, its role in tissue-specific expression is not known. For example, differing modes of its recognition by general transcription machinery can provide an additional layer of control within which a single tissue-restricted transcription factor may operate. Erythroid Kruppel-like factor (EKLF) is a hematopoietic-specific transcription factor that is critical for the activation of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
(77 reference statements)
0
30
0
Order By: Relevance
“…However, like other acidic TADs, it is thought that EKLFTAD participates in interactions with transcriptional regulatory factors such as general transcription factors, chromatin remodeling complexes, and HATs (12)(13)(14)16). In this article, we demonstrate that EKLFTAD displays sequence homology to the p53TAD and contains two functional subdomains (EKLF-TAD1 and EKLFTAD2).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…However, like other acidic TADs, it is thought that EKLFTAD participates in interactions with transcriptional regulatory factors such as general transcription factors, chromatin remodeling complexes, and HATs (12)(13)(14)16). In this article, we demonstrate that EKLFTAD displays sequence homology to the p53TAD and contains two functional subdomains (EKLF-TAD1 and EKLFTAD2).…”
mentioning
confidence: 80%
“…Like the DBD, the TAD plays an important role in EKLF's ability to activate β-globin expression (16)(17)(18). Initial experiments demonstrated that the first 100 residues constituted the minimal TAD of EKLF (EKLFTAD) (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, enhancer-bound transcription factors can activate the transcription of natural target genes that have different core promoter elements and depend on different basal transcription factors. For example, the mouse hematopoietic-specific transcription factor EKLF (erythroid Krupple-like factor, or KLF1) activates the transcription of both the adult -globin gene and the Ahsp (-hemoglobin-stabilizing protein) gene, but -globin transcription depends on its core promoter DCE and on a particular basal transcription factor (the TFIID subunit TAF9, as discussed below), whereas the Ahsp core promoter lacks a DCE and its transcription is TAF9 independent (Sengupta et al, 2009). Thus, enhancer elements and transcription factors are often compatible with multiple core promoter elements and basal transcription factors.…”
Section: Enhancer-core Promoter Element Specificitymentioning
confidence: 99%
“…S5). The β-globin and BKLF promoters share some similarities in their promoter architecture (e.g., INI and DPE elements), unlike the AHSP promoter (46). In addition, EKLF/TAF9 interactions are critical for β-globin but not AHSP promoter activity.…”
Section: Significancementioning
confidence: 99%